Generation of ideal thermal light in warm atomic vapor. (5th September 2018) - Mika, J; Podhora, L; Lachman, L; Obšil, P; Hloušek, J; Ježek, M; Filip, R; Slodička, L
Abstract: We present the experimental generation of light with directly observable close-to-ideal thermal statistical properties. The thermal light state is prepared using a spontaneous Raman emission in a warm atomic vapor. The photon number statistics are evaluated by both the measurement of second-order correlation function and by the detailed analysis of the corresponding photon number distribution, which certifies the quality of the Bose–Einstein statistics generated by a natural physical mechanism. We further demonstrate the extension of the spectral bandwidth of the generated light to hundreds of MHz domain while keeping the ideal thermal statistics, which suggests a direct applicability of the presented source in a broad range of applications including optical metrology, tests of robustness of quantum communication protocols, or quantum thermodynamics.